Positive Association Between Plasma Aldosterone Concentration and White Matter Lesions in Patients With Hypertension - Yuan, Yujuan; Li, Nanfang; Liu, Yan; Zhu, Qing; Heizhati, Mulalibieke; Zhang, Weiwei; Yao, Xiaoguang; Zhang, Deilian; Luo, Qin; Wang, Menghui; Chang, Guijuan; Cao, Mei; et al. (Frontiers in Endocrinology, 2021)
Background and objective: White matter lesions (WMLs) are imaging changes in MRI of cerebral small vessel disease associated with vascular risk factors, increasing the risk of dementia, depression and stroke. We aimed to analyze the relationship between ALD and WMLs in population with hypertension. Methods: We conducted a retrospective review of all patients screened for causes of secondary hypertension. We enrolled 547 patients with WMLs and matched these to controls without WMLs at a 1:1 ratio. White matter lesion load was assessed by using a modified Scheltens scale. Results: Among the analytic sample (N=1094) with ages ranging from 30 to 64 years, 62.2% were male. We divided plasma aldosterone concentration (PAC), plasma renin activity (PRA), and aldosterone-renin ratio (ARR) into the third tertile (Q3), second tertile (Q2) and first tertile (Q1). We also analyzed them simultaneously as continuous variables. Multivariate logistic regression analysis showed that participants in Q3 (>17.27 ng/dl) of PAC (OR 1.59, 95% CI 1.15, 2.19), Q3 (<0.80 ng/dl) of PRA (OR 2.50, 95% CI 1.81, 3.44) and Q3 (>18.60 ng/dl per ng/ml*h) of ARR (OR 2.90, 95% CI 2.10, 4.01) had a significantly higher risk of WMLs than those in Q1 (<12.48) of PAC, Q1 (>2.19) of PRA and Q1 (<6.96) of ARR. In linear regression analysis, we separately analyzed the correlation between the modified Scheltens scale score and log (PAC) (β= 2.36; 95% CI 1.30, 3.41; P<0.001), log (PRA) (β= -1.76; 95% CI -2.09,-1.43; P<0.001) and log (ARR) (β= 1.86; 95% CI 1.55, 2.17; P<0.001), which were all significantly correlated with white matter lesion load after adjusting for confounding factors. Simple mediation analyses showed that systolic blood pressure (SBP) or diastolic blood pressure (DBP) mediated -3.83% or -2.66% of the association between PAC and white matter lesion load, respectively. In stratified analyses, there was no evidence of subgroup heterogeneity concerning the change in the risk of WMLs (P > 0.05 for interaction for all). Conclusion: Higher PAC, especially in PAC >17.27 ng/dl, increased the risk of WMLs. PAC was positively associated with white matter lesion load independent of SBP or DBP.